Rothman Institute manual of total joint arthroplasty : protocol-based care - Hojack, William J.; Parvizi, Javad; Sharkey, Peter F. (New Delhi, India : Jaypee Brothers Medical Publishers, 2017)
This book is a complete guide to total joint arthroplasty for orthopaedic surgeons presented as a collection of key protocols for surgery. Divided into four sections, the text begins with preoperative considerations, covering patient evaluation, clinical examination, indications, and implant selection. The following section provides step by step guidance on the complete range of arthroplasty techniques and associated procedures. Section three covers postoperative management such as wound care, transfusions, physical therapy, medication, and much more. The final chapters in the book discuss the management of numerous potential complications. Edited by an internationally recognised team of experts, led by Javad Parvizi from the renowned Rothman Institute in Philadelphia, this comprehensive guide is enhanced by surgical images and diagrams to assist learning
Preoperative -- Perioperative -- Postoperative managment -- Complications.
Keywords: Arthroplasty, Replacement, Hip; Total hip replacement; Total knee replacement